Metode dan Strategi Pembelajaran Medication Administration pada Pendidikan Keperawatan untuk Mencegah Medication Error - Dianti, Puteri; Musharyanti, Lisa (Journal of Telenursing (JOTING), 2024)
This research aims to identify various learning methods that have been used in teaching medication safety. The research method is a scoping review where articles are taken from several databases such as PubMed, ProQuest, Science Direct, and Springer Link from year to year. Keywords used include "learning methods", "learning strategies", "drug administration", and "nursing education". The results obtained by researchers found several learning strategies used in the drug administration learning process based on literature searches. In conclusion, several learning strategies used are simulation-based, 3D game simulation, Computer-Based Virtual Learning Environment (CBVLE), and Web-Based Virtual Learning Environment. Other methods include training based on the Teaching for Understanding (TfU) framework, lecture demonstration & video demonstration, flipped classroom (FC) learning with a near-peer education (NPE) approach, Medication Error Encouragement Training (MEET), and drug safety training using the 4C approach /ID. Keywords: Medication Administration, Medication Error, Learning Methods, Learning Strategies, Nursing Education.